2023
DOI: 10.3389/fendo.2023.1129793
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for diabetes management during COVID-19: what we have learnt, what and how to implement

Abstract: The past two decades have witnessed telemedicine becoming a crucial part of health care as a method to facilitate doctor-patient interaction. Due to technological developments and the incremental acquisition of experience in its use, telemedicine’s advantages and cost-effectiveness has led to it being recognised as specifically relevant to diabetology. However, the pandemic created new challenges for healthcare systems and the rate of development of digital services started to grow exponentially. It was soon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Our research shows that using telemedicine to help people with DM has a positive effect on their health, which is in line with what other studies have found (AlMutairi et al, 2021; De Groot et al, 2021 ; Su et al, 2016; Zhang et al, 2022 , Lee et al, 2019 , Santos et al, 2022 , Aberer et al, 2021 , Rosta et al, 2023 ). Patients who used telemedicine had substantially better glycemic control than those who received only in-person care.…”
Section: Discussionsupporting
confidence: 92%
“…Our research shows that using telemedicine to help people with DM has a positive effect on their health, which is in line with what other studies have found (AlMutairi et al, 2021; De Groot et al, 2021 ; Su et al, 2016; Zhang et al, 2022 , Lee et al, 2019 , Santos et al, 2022 , Aberer et al, 2021 , Rosta et al, 2023 ). Patients who used telemedicine had substantially better glycemic control than those who received only in-person care.…”
Section: Discussionsupporting
confidence: 92%
“…Telemedicine emerges as a potential solution to address the imbalanced distribution of medical resources. The World Health Organization (WHO) defines telemedicine as a medical service provided where distance is a critical factor, and medical service providers apply different communication technologies to overcome these distance-related issues [3] . The goal is to share information necessary for diagnosis, prevention, and therapy of disease [3] .…”
Section: Preprint Settingsmentioning
confidence: 99%
“…The World Health Organization (WHO) defines telemedicine as a medical service provided where distance is a critical factor, and medical service providers apply different communication technologies to overcome these distance-related issues [3] . The goal is to share information necessary for diagnosis, prevention, and therapy of disease [3] . Through telemedicine, patients can access a doctor while avoiding access barriers, such as clinic wait times, less travel time, and time off from work.…”
Section: Preprint Settingsmentioning
confidence: 99%
“…And with the continuous development of Internet, it has gradually formed two categories: medical and health apps using mobile terminal systems such as Android and IOS, and software that can detect human body data and analyze the results ( 6 , 7 ). Numerous experiments have shown that patients’ glycemic control and self-management abilities improve with telemedicine participation, and it has a positive impact on patients’ psychosocial factors ( 8 , 9 ). Guo et al ( 10 ) used an implantable glucose sensor and a mobile application to intervene in the DSM of patients with T2DM, and they found that body mass index (BMI), fasting blood glucose (FBG), postprandial 2-h blood glucose (2hPG) and glycosylated hemoglobin (HbA1c)in intervention groups were lower than those of control groups, and the quality of life and DSM ability of patients in intervention groups were significantly improved ( 10 ).…”
Section: Introductionmentioning
confidence: 99%